2018
DOI: 10.1111/odi.12889
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoking decreases clinical symptoms of gingivitis in patients with type 1 diabetes—a cross‐sectional study

Abstract: Patients with type 1 diabetes smoking cigarettes presented lower gingival sulcus bleeding and worse metabolic control of diabetes than nonsmoking patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…AGEs are heterogeneous compounds mainly derived from the nonenzymatic glycation (Maillard reactions) of reducing sugar on proteins, lipids, and nucleic acids. AGEs can increase reactive oxygen species (ROS) production, thereby initiating intracellular oxidative stress [ 22 ]. Conversely, the increase in ROS production can promote the production of AGEs, thereby forming a vicious circle between oxidative stress and AGEs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGEs are heterogeneous compounds mainly derived from the nonenzymatic glycation (Maillard reactions) of reducing sugar on proteins, lipids, and nucleic acids. AGEs can increase reactive oxygen species (ROS) production, thereby initiating intracellular oxidative stress [ 22 ]. Conversely, the increase in ROS production can promote the production of AGEs, thereby forming a vicious circle between oxidative stress and AGEs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that infection in periodontal tissue disease might be one of the clinical manifestations of chronic inflammation in type 1 diabetes [ 22 , 23 , 24 ]. It is also well established that chronic hyperglycemia and oxidative stress lead to an imbalance between the opportunistic bacteria of biofilm and the host immune response in the oral cavity environment, which results in inflammation and the possible destruction of periodontal tissue [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Tarnowski made and interesting observation when comparing smokers with type 1 diabetes with non-smoker diabetic patients. BOP was lower in the smoker group, demonstrating the negative effect of smoking on microvascular circulation (108).…”
Section: Diabetes Mellitusmentioning
confidence: 78%